Psychometrics in Parenting Capacity Assessments: A problem for Aboriginal parents - Choate, Peter; McKenzie, Amber (First Peoples Child & Family Review, 2015)
Parenting Capacity Assessments (PCA) are used by child protection workers to assist in determining the ability of a parent to care for their children. They may be used at various stages of the case management process but these assessments serve as powerful tools for decision making by these workers. They can also be introduced in court as part of expert testimony. Most PCAs utilize psychometric assessment measures to elicit data in respect to personality, parenting knowledge, as well as mental health and addiction issues. The authors argue that the norming of these measures has insufficient inclusion of Aboriginal peoples to be used for assessments with this population. They further argue that different approaches need to be developed as current approaches, including assessment measures, are based upon the constructs of the dominant culture, which is individualistic as opposed to the Aboriginal collectivistic approaches to parenting.